Экспериментально-расчетная методика определения комплексных проницаемостей ферромагнитных композитов - Demianchuk, B. A. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A method is proposed for determining the components of complex permeabilities of composites within a specified frequency range. The parameters are calculated from measured data on the traveling-wave coefficient and wavelength in an open and short-circuited waveguide with a probe, as well as on the displacement of the first field minimum from the sample under the same conditions. The modernization of the method made it possible to ensure the required accuracy and, above all, the unambiguity of the results.